How Does Job Well-Being Optimize Audit Performance? The Moderating Effect of Passion - Kuo-Chih Cheng; Yuan-Sheng Lin; Tung-Chin Yang; Tsung-Fu Chuang; Hsiu-Mei Lai; Lan-Hui Lin; Shao-Hsi Chung (Behavioral Sciences)
Most prior studies found that job well-being and job performance are in a linear relationship. Audit firms are a type of highly professional organization. Based on the affective events theory, this study argues that job well-being can accelerate the improvement of audit performance thus forming a curvilinear relationship. Additionally, auditing is a job that demands highly professional skills and responsibility. This study argues that an auditor’s passion for work can strengthen the relationship between job well-being and audit performance. The study employed a quantitative survey approach, collecting data from 178 auditors who are in a position of in-charge, deputy manager, and manager in the Big Four CPA firms in Taiwan. The empirical evidence confirmed that job well-being and audit performance are in a curvilinear relationship. In addition, the effect of job well-being on audit performance is greater in the presence of high passion and will diminish when the passion is low. According to the research results, the managerial implications for audit firms are provided.